1998
DOI: 10.1161/01.cir.98.22.2415
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Transluminal Septal Myocardial Ablation in Hypertrophic Obstructive Cardiomyopathy

Abstract: Background —Percutaneous transluminal septal myocardial ablation (PTSMA) has been introduced as an alternative procedure for reducing the left ventricular outflow tract gradient (LVOTG) in hypertrophic obstructive cardiomyopathy. We report on the acute and mid-term results in 91 symptomatic patients with respect to intraprocedural myocardial contrast echocardiography (MCE). Methods and Results —PTSMA was intended for 46 women and 45 men (54.1±15.5 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
138
0
8

Year Published

1999
1999
2004
2004

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 287 publications
(153 citation statements)
references
References 29 publications
7
138
0
8
Order By: Relevance
“…1,3 There has been considerable interest over the past few years in a percutaneous method for relieving obstruction and symptoms that has been referred to in the literature by several names and acronyms. [3][4][5][6][7][8][9] This procedure uses conventional interventional methodology currently available for treating atherosclerotic coronary artery disease to create necrosis of the anterior basal septum by introducing absolute alcohol directly into a proximal septal perforator artery, ultimately reducing LV wall thickness, enlarging the outflow tract and reducing mechanical impedance to LV ejection. Therefore, percu-taneous transluminal septal myocardial ablation (PTSMA) may mimic the morphological and hemodynamic effects of surgical myectomy.…”
Section: Therapeutic Options In Obstructive Hcmmentioning
confidence: 99%
See 3 more Smart Citations
“…1,3 There has been considerable interest over the past few years in a percutaneous method for relieving obstruction and symptoms that has been referred to in the literature by several names and acronyms. [3][4][5][6][7][8][9] This procedure uses conventional interventional methodology currently available for treating atherosclerotic coronary artery disease to create necrosis of the anterior basal septum by introducing absolute alcohol directly into a proximal septal perforator artery, ultimately reducing LV wall thickness, enlarging the outflow tract and reducing mechanical impedance to LV ejection. Therefore, percu-taneous transluminal septal myocardial ablation (PTSMA) may mimic the morphological and hemodynamic effects of surgical myectomy.…”
Section: Therapeutic Options In Obstructive Hcmmentioning
confidence: 99%
“…4 Most other PTSMA practitioners utilize myocardial contrast echocardiography to identify the appropriate septal perforator, which involves 2-dimensional echocardiographic monitoring during introduction of 1 to 2 mL of echo or angiographic contrast through the distal lumen of a balloon dilation catheter. 5,6 Contrast echocardiography enhances the effectiveness and safety of PTSMA by avoiding arteries that supply distant regions of myocardium, as well as by limiting the number of arteries intervened, the frequency of complete heart block requiring permanent pacemaker, the amount of alcohol injected (and creatine phosphokinase levels), and fluoroscopy time. After identification of the most appropriate perforator, balloon occlusion is followed by contrast injection through the coronary guide catheter as well as the distal balloon port to document complete cessation of flow between the distal septal artery and LAD.…”
Section: Ptsma Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…4 Knight et al 5 and Seggewiss et al 6 have both reported that PTSMA significantly reduces LVOT obstruction and improves the symptoms in HOCM, but it has also been reported that permanent pacemaker implantation was required in 20% of the patients because of complete atrioventricular block associated with this procedure. Faber et al 7 reported that myocardial contrast echocardiography (MCE) for target vessel selection in PTSMA improved both the acute and chronic results. We describe a case of HOCM treated by PTSMA in which intraprocedural selective MCE was very helpful in identifying the culprit septal branch.…”
mentioning
confidence: 99%